Doing the Work, Considering the Entanglements of the Research Team While Undoing Settler Colonialism - Loncon-Antileo, E (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2019)
This paper presents the work of three researchers in a self-study on researcher positionality using the reflective practice and pedagogy of correspondence as preparation for future work with mapuche women in Chile. We start from the assumption that research with and on indigenous groups has a historical debt to consider given the ways in which it has historically perpetuated and been complicit in violence against indigenous people. With this is mind we ask: what can a focus on researcher s positionality and epistemologies bring to future work on mapuche women s educational experience? What does it contribute to work that refuses the violence that academia perpetuates on indigenous knowledges and communities? This paper is an invitation to reflect on how we can decolonize our methodologies as a way to work through the historical debt that academia has with and to indigenous groups.